2006
DOI: 10.1111/j.1464-410x.2006.06224.x
|View full text |Cite
|
Sign up to set email alerts
|

Flap endonuclease 1 is overexpressed in prostate cancer and is associated with a high Gleason score

Abstract: array. FEN-1 nuclear expression was scored based on the percentage of target cells staining positively, and correlated with Gleason score, preoperative prostate-specific antigen (PSA) level and pathological stage. The time to PSA recurrence was also analysed. RESULTSThe mean expression of FEN-1 was significantly higher in cancer (36.7%) than in normal (13.2%), BPH (4.5%) and PIN (15.4%) specimens ( P < 0.001). FEN-1 expression was significantly correlated with Gleason score (ó = 0.23, P = 0.002). A higher preo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
75
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 91 publications
(81 citation statements)
references
References 49 publications
6
75
0
Order By: Relevance
“…These mutations abolish the exonuclease activity but retain the flap endonuclease activity (Zheng et al, 2007), which is consistent with the finding that mice carrying mutations show higher chemically induced cancer incidence (Xu et al, 2011). The mutations of FEN1 in PC are yet to be investigated, however, FEN1 has been reported to be overexpressed in PC, especially in high Gleason score tumors (Lam et al, 2006). Here, we showed that the high frequency of nuclear staining was found significantly (Po0.0001) more often in CRPC than in PC, and that the staining was associated with poor prognosis in prostatectomy-treated patients.…”
Section: Ar Overexpression Enhances Receptor Binding To Chromatinsupporting
confidence: 74%
“…These mutations abolish the exonuclease activity but retain the flap endonuclease activity (Zheng et al, 2007), which is consistent with the finding that mice carrying mutations show higher chemically induced cancer incidence (Xu et al, 2011). The mutations of FEN1 in PC are yet to be investigated, however, FEN1 has been reported to be overexpressed in PC, especially in high Gleason score tumors (Lam et al, 2006). Here, we showed that the high frequency of nuclear staining was found significantly (Po0.0001) more often in CRPC than in PC, and that the staining was associated with poor prognosis in prostatectomy-treated patients.…”
Section: Ar Overexpression Enhances Receptor Binding To Chromatinsupporting
confidence: 74%
“…In primary prostate cancer from two hundred and forty six patients who had had a radical prostatectomy, FEN-1 nuclear expression correlated with Gleason score. These results suggest that FEN-1 might be a potential marker for selecting patients at high risk and therapy [84]. Interestingly, synthetic lethality (SL) has been observed in RAD54B-deficient human colorectal cancer cell line by iatrogenic reduction of FEN1 expression thus demonstrating it to be a potential novel therapeutic biological target [85].…”
Section: Fen1mentioning
confidence: 87%
“…Using cancer profiling array and immune-histochemistry, we have previously found that FEN1 is clearly over-expressed in breast cancer tissues [22]. In addition, FEN1 is also highly expressed in lung [25] and gastric cancer cell lines [26], as well as prostates cancer [21,27], neuroblastomas [28], testis, lung, and brain tumors in situ [7]. Interestingly, FEN1 is significantly up-regulated in mouse fibroblasts in a p53-dependent manner under genome toxic stresses such as exposure to UV-C [29] and DNA-alkylating drugs [30].…”
Section: Introductionmentioning
confidence: 99%